Management of childhood pain and healthcare providers’ willingness to use topical anaesthetic cream for minor procedural pain in Nigeria (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Abstract: Objective: To determine providers’ willingness to use (WTU) topical anaesthetic cream (TAC) to alleviate childhood pain.This information will be useful for successful implementation of TAC in Nigeria. Subjects and Methods: The study was undertaken in hospitals in southeast Nigeria. Intervieweradministered questionnaire was used to collect information: on the providers’ preferred waiting time and their WTU TAC. Likert scale was used to assess the providers’ level of uneasiness when performing painful procedures and their WTU the TAC. Multiple regression analyses were performed to measure the relationship of WTU with the different independent variables, after creating a binary option for some variables.Results: Providers surveyed were 232. Majority (94.8%) wanted the pain alleviated and 87.9% had made some attempts to alleviate the pain. Only one respondent (1%) knew about TAC, but none had used it before. Over 94% of the respondents were WTU TAC. The mean maximum preferred waiting time was 37.03 minutes. Many (68.8%) were concerned about the prolonged waiting time required and 19.8% and 12.5% with its availability and affordability respectively. In linear multivariate analyses, WTU was not statistically associated with designation, age, average weekly procedure and scale-rating of the childhood pain (p > 0.05).Conclusion: The WTU TAC was high, but the mean time willing to wait was lesser than mean recommended time of 45 minutes. If this latter limitation is circumvented, it may aid implementing the use of TAC in routine pediatric care.Keywords: Nigeria; Willingness to Use; Topical Anaesthetic Cream; Providers.